(untitled) (The Review of Diabetic Studies, 2024)
The article analyzes the role of the informal caregiver, understood as the person who provides unpaid support to individuals with disabilities, dependency or chronic diseases. It is stated that this work, carried out by millions of people in the world – mainly women – involves a high physical, emotional, social and economic burden that affects multiple dimensions of the caregiver’s life. The text addresses the commitments and meanings of care, showing that the caregiver faces difficulties such as lack of institutional support, lack of training, feelings of guilt, frustration and helplessness, especially when the patient’s dependence is severe. Likewise, the four phases that the caregiver goes through when assuming the role are described: denial, search for information, restructuring and conclusion, highlighting the importance of the adaptation process. The essay also delves into the holistic effects of care on caregiver health, pointing out negative physical (chronic pain, sleep disorders, hypertension), emotional (stress, depression, exhaustion) and social (isolation, changes in leisure activities, family overload) impacts. Caregiver Syndrome, described as a response to chronic stress, is addressed and the factors that influence "caregiver role fatigue" are mentioned, according to the NANDA taxonomy. Finally, the article highlights the urgent need to recognize the informal caregiver as a subject of care within public policies and health systems, emphasizing the role of nursing in accompaniment, burnout prevention, emotional support, and strengthening caregiver self-care.